Inorganic nanomaterials for supercapacitor design - Inamuddin, 1980-; Boddula, Rajender; Ahamed, Mohd Imran; Asiri, Abdullah M. (CRC Press, 2020)
"Inorganic electrode materials are used in high-performance energy conversion and storage due to their redox chemistry, chemical stability, high electrochemical performance, and high-power applications. An international team of experts explore and review advances in inorganic nanomaterials for supercapacitor energy storage devices"--